Mukwahepo: Woman, soldier, mother: As told to Ellen Ndeshi Namhila. Windhoek: University of Namibia Press, 2013; pp 141. (Journal for Studies in Humanities and Social Sciences, 2015)
Unlike many stories that deal with high ranking and public fi gures, Mukwahepo is a book about a humble and unknown personality who made outstanding and remarkable contributions to the liberation of Namibia, popularly called The Land of the Brave. Mukwahepo is an ordinary woman who performed extraordinary duties for her country. This book is a clear testimony that the contributions, especially those made by women, did not have to be ambassadorial or political.